Research on Influencing Factors of Cross Border E-Commerce Supply Chain Resilience Based on Integrated Fuzzy DEMATEL-ISM - Xianli Liu (IEEE Access, 2021)
Supply chain resilience is the key for cross-border e-commerce enterprises to continuously obtain competitive advantages. This paper studies the influencing factors of cross-border e-commerce supply chain resilience (CBSCR), so as to further enhance the competitiveness of global supply chain and ensure the safe operation of cross-border e-commerce supply chain. Based on the ternary theory of supply chain resilience, this paper firstly constructs the CBSCR influencing factor system, and then analyzes the comprehensive influence degree, causal relationship and logical hierarchy among the influencing factors by using the fuzzy DEMATEL-ISM method. The results show that: recovery speed of supply chain disruption, response time of supply chain disruption, coordination ability among cross border e-commerce partners, experience sharing among cross-border e-commerce partners, joint planning among cross-border e-commerce partners, establish a good enterprise reputation for fairness, risk management team among partners, and develop a collaborative culture among partners are the key influencing factors of CBSCR. On this basis, it is proposed that the adaptability of supply chain is a top priority, which can be started from strengthening risk management culture, cooperation among partners and construction of supply chain agility.